A Novel MFS-MDR Transporter, MdrP, Employs D223 as a Key Determinant in the Na+ Translocation Coupled to Norfloxacin Efflux - Zhang, Rui; Abdel-Motaal, Heba; Zou, Qiao; Guo, Sijia; Zheng, Xiutao; Wang, Yuting; Zhang, Zhenglai; Meng, Lin; Xu, Tong; Jiang, Juquan (Frontiers in Microbiology, 2020)
Multidrug resistance (MDR) transporters of the major facilitator superfamily (MFS) were previously believed to drive the extrusion of multiple antimicrobial drugs through the coupling to proton translocation. Here we present the identification of the first Na+-coupled MFS-MDR transporter, MdrP, which also can achieve H+-coupled drug efflux independently of Na+. Importantly, we propose that MdrP can extrude norfloxacin in a mode of drug/Na+ antiport, which has not yet been reported in any MFS member. On this basis, we further provide the insights into a novel Na+ and H+ coupling mechanism of MFS-MDR transporters, even for all secondary transporters. The most important finding lies in that D223 should mainly act as a key determinant in the Na+ translocation coupled to norfloxacin efflux. Furthermore, our results partially modify the knowledge of the conformational stability-related residues in the motif A of MFS transporters, and imply the importance of a new positively-charged residue, R361, for the stabilization of outward-facing conformation of MFS transporters. These novel findings positively contribute to the knowledge of MFS-MDR transporters, especially about Na+ and H+ coupling mechanism. This study is based mainly on measurements in intact cells or everted membranes, and a biochemical assay with a reconstitued MdrP protein should be necessary to come to conclusion to be assured.